Lesbian Gay Bisexual Transsexuals and Patient Rights - Yeşiltepe, Gözde; Özdemir, Mehmet Hakan (The Bulletin of Legal Medicine, 2023)
Objective: The aim of this study is to determine the discrimination faced by LGBT, and violation of their rights based on their gender identity or sexual orientation while receiving health care.Methods: Our study was conducted as a cross-sectional survey study. LGBT individuals were contacted through the Black Pink Triangle Izmir Association; For Researches On & Against Discrimination Based On Sexual Orientation and Gender Identity. Questions of our survey were compiled from items of Turkish Patient Rights Regulation and questionnaires which were used in “Surveillance Report of Discrimination Based on Sexual Orientation and Gender Identity in Türkiye” study. Results: Sixty-three LGBT individuals were included in this study. Forty-four of the participants (69.8%) were homosexual/lesbian or gay, 11 of them were bisexual (17.5%) and eight of them (12.7%) were transgender. 84.1% (53) of the participants had health insurance. We found that transgenders were exposed to discrimination significantly more than bisexuals and homosexuals (p=0.042). Fourteen individuals claimed that they were exposed to discrimination based on their gender identity or sexual orientation: 11 of them were discriminated by physicians (78.56%).Conclusion: We found that LGBT individuals face discrimination more than the general population and usually receive health care in inconvenient conditions. We believe that starting from health care providers, public awareness should be raised about discrimination rates, and also a health care policy should be developed and an action policy should be planned about the discrimination of LGBT individuals.